Response of growing and finishing swine to a dietary source of lactobacillus acidophilus - Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Post-weaning comparisons were made using high and low protein rations with and without a fermentation product (lactobacillus acidophilus). Pigs receiving higher protein rations (18%) grew slightly faster than those receiving low protein (15%) rations; however, the differences were not significant. Adding a fermentation product to either ration tested did not significantly improve performance of weaned pigs. Finishing swine were used to compare high-protein (16%) ration and low-protein (13%) rations with and without the fermentation product. Pigs receiving the higher-protein ration grew significantly faster than those receiving the lower-protein ration with or without the additive. Pigs receiving the additive in the 13% ration grew slightly faster than pigs receiving the 13% ration without the additive.
Swine Industry Day 1971 is known as Swine Day, 1971
Keywords: Swine; Growing pigs; Finishing pigs; Lactobacillus acidophilus